Climate regulation and financial risk: The challenge of policy uncertainty - Tobias Berg; Elena Carletti; Stijn Claessens; Jan Pieter Krahnen; Irene Monasterolo; Marco Pagano (Leibniz Institute for Financial Research SAFE, 2023)
Climate risk has become a major concern for financial institutions and financial markets. Yet, climate policy is still in its infancy and contributes to increased uncertainty. For example, the lack of a sufficiently high carbon price and the variety of definitions for green activities lower the value of existing and new capital, and complicate risk management. This column argues that it would be welfare-enhancing if policy changes were to follow a predictable longer-term path. Accordingly, the authors suggest a role for financial regulation in the transition.
Keywords: 330; Climate Change; Financial Regulation and Banking